Butene-1 polymer composition with short crystallization time

JP7631499B2Active Publication Date: 2025-02-18BASELL POLIOLEFINE ITALIA SRL
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023505375
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-31
Filing Date
2021-07-28
Publication Date
2025-02-18
Estimated Expiration
2041-07-28

Smart Images

  • Figure 0007631499000001
    Figure 0007631499000001
  • Figure 0007631499000002
    Figure 0007631499000002
  • Figure 0007631499000003
    Figure 0007631499000003
Patent Text Reader

Abstract

The present disclosure relates to a butene-1 polymer composition that is particularly suitable for the manufacture of tubing, comprising: A) 97.5% to 99.85% by weight, relative to the total weight of A) and B), of a butene-1 polymer or polymer composition; B) 0.15% to 2.5% by weight, relative to the total weight of A) and B), of talc in particulate form having a volumetric particle size distribution Dv(0.95) of less than or equal to 45 μm; and optionally C) 0.01% to 2% by weight of an ethylene polymer, the amount of C) meaning the total weight of A)+B)+C), which totals 100%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to butene-1 polymer compositions having reduced crystallization times. [Background technology]

[0002] Butene-1 polymers are known in the art and have a wide range of applications, in particular butene-1 homopolymers and copolymers with high crystallinity are usually characterized by their excellent performance in terms of pressure resistance, creep resistance, impact strength, and are useful for the manufacture of pipes that can replace metal pipes.

[0003] One of the key requirements for these applications in the tubing industry is a good combination of flexibility and tensile strength.

[0004] Furthermore, in order to achieve high speeds during extrusion, the crystallization time must be sufficiently short in the tubing forming process, which is usually performed by extrusion.

[0005] More generally, short crystallization times are beneficial in many polymer processing processes and favor high processing rates.

[0006] It is known in the art to affect this performance by adding nucleating agents, which are usually foreign (heterogeneous nucleation) that promote crystallization of the polymer from the melt.

[0007] Although many nucleating agents have been found to be effective in crystalline polymers, in the field of olefin nucleation, a nucleating agent effective for one polymer may be ineffective for a closely related polymer, making it difficult to identify the most suitable nucleating agent for a particular polymer, especially a butene-1 polymer that has crystallized in at least two different crystalline forms.

[0008] Furthermore, it is conceivable that the required performance differs depending on the application.

[0009] For example, during use of pipe materials, excessive bending stiffness (high bending elasticity modulus) This is because, as mentioned above, a certain degree of flexibility is required.

[0010] However, if the flexural modulus is too low, the long-term pressure resistance decreases.

[0011] Also, a crystallization time that is too low is a drawback since it becomes difficult to consistently produce tubing with the desired shape and performance.

[0012] For this reason, efforts are being made in this field to develop nucleating agents that provide the best balance of mechanical and processability properties depending on the type of polymer used and the required application.

[0013] For example, according to JP2007186563, the addition of ethylene bisstearamide and talc to butene-1 polymers provides a balance of performance for tubing applications.

[0014] It has now been discovered that butene-1 polymer compositions having a particularly valuable balance of crystallization time, flexural modulus and tensile strength can be obtained by adding relatively low amounts of talc having a particular particle size. Summary of the Invention [Problem to be solved by the invention]

[0015] For this reason, the present disclosure: 97.5% to 99.85% by weight, preferably 98% to 99.8% by weight, more preferably 98% to 99.5% by weight, of a polymer composition selected from butene-1 polymers or crystalline butene-1 homopolymers, copolymers or combinations thereof, based on the total weight of A) and B), 0.15% to 2.5% by weight, preferably 0.2% to 2% by weight, more preferably 0.5% to 2% by weight, of talc in particulate form, based on the total weight of A) and B), having a volumetric particle size distribution Dv(0.95) determined by laser diffraction of 45 μm or less, preferably 35 μm or less, more preferably 25 μm or less, in particular 20 μm or less, with a lower limit of preferably 5 μm in each case, and optionally 0.01% to 2% by weight, preferably 0.01% to 1% by weight, more preferably 0.01% to 0.5% by weight, particularly 0.01% to 0.2% by weight of an ethylene polymer, The amount of C) refers to the total weight of A)+B)+C) providing a butene-1 polymer composition that totals 100%. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] "Crystalline butene-1 homopolymers and copolymers" refers to those homopolymers and copolymers A) that exhibit a crystallization temperature T c This means that the crystallization exhibits at least one crystallization peak corresponding to

[0017] Thus, when subjected to DSC measurements, the inventive butene-1 polymer composition comprising components A), B) and optionally C) also exhibits at least one crystallization peak and therefore a crystallization temperature T c Shows.

[0018] Preferably, the T of the butene-1 polymer component A) c The value is above 75°C, particularly in the range of 75°C to 85°C.

[0019] The T of the butene-1 polymer composition of the present invention c The value is preferably 80°C or higher, particularly in the range of 80°C to 90°C.

[0020] The T of the butene-1 polymer composition of the present invention c The value is preferably T cat least 2°C higher than the value, especially 2°C to 5°C higher.

[0021] The crystallization temperature is measured after one melt cycle with a scan rate of 10° C. / min.

[0022] Thus, upon initial melting of a molten polymer sample followed by a cooling run, a crystallization temperature is measured (eg, using DSC prior), and such crystallization temperature is attributed to crystalline Form II of the butene-1 polymer.

[0023] If more than one crystallization peak is detected, the temperature of the most intense peak is taken as the Tc value of both the butene-1 polymer component A) and the butene-1 polymer composition of the present invention.

[0024] As mentioned above, the butene-1 polymer compositions of the present invention have short crystallization times.

[0025] Preferably, the crystallization half time at 90° C. is 90 to 160 seconds, particularly 100 to 150 seconds.

[0026] This determination is made by DSC, which first melts the sample, then rapidly cools it to the desired temperature (in this case 90°C), and measures the heat flow due to the release of heat from crystallization. The integral of the heat transfer is recorded as a function of time until crystallization is complete, i.e., when heat transfer stops.

[0027] The crystallization half-time is the time for the heat transfer integral to reach half its final value.

[0028] Furthermore, the butene-1 polymer compositions of the present invention preferably have at least one of the following additional characteristics: A flexural modulus of 450-650 MPa, more preferably 500-600 MPa, measured according to standard ISO 178:2019 after 10 days of molding; a tensile modulus of 500-800 MPa, more preferably 560-750 MPa, measured on a 1 mm thick compression moulded plaque by DMTA analysis at 23 °C in accordance with ISO 6721-4:2019; 3-15 kJ / m measured according to IS0180:2000 on compressed plaque according to ISO 8986-2:2009 2 , especially 3-10 kJ / m 2 Izod impact resistance value at 23°C; 2-10 kJ / m, measured according to ISO 8986-2:2009 on compressed plaques according to IS0180:2000 2 , especially 2-8 kJ / m 2 Izod impact resistance value at 0°C.

[0029] The butene-1 homopolymers and copolymers A) are preferably highly isotactic linear polymers, in particular having a degree of isotacticity of 90% to 99%, more preferably 95% to 99%, as measured by NMR analysis in mmmm pentads / total pentads or as measured by the amount by weight of material soluble in xylene at 0° C.

[0030] Furthermore, the butene-1 homopolymers and copolymers A) preferably have at least one of the following characteristics: X-ray crystallinity of 50%-60%; 0.90~0.94 g / cm 3 Density.

[0031] Preferably, the butene-1 homopolymers and copolymers A) and the butene-1 polymer compositions of the invention comprising components A), B) and optionally C) have a melting temperature (melting peak) of 90-125°C, more preferably 100-125°C, measured by the above mentioned DSC method at a scanning rate of 10°C / min during the second heating run after the first melting and cooling.

[0032] Said melting temperature is attributed to the crystalline form II of the butene-1 polymer.

[0033] Again, if one or more melt peaks are detected, the temperature of the closest peak is taken as the melt temperature.

[0034] Suitable butene-1 copolymers are those copolymers which preferably contain up to 5 mol %, in particular 0.1 mol % to 5 mol %, more preferably 0.1 mol % to 3 mol % of an olefinic comonomer. The comonomer is usually ethylene, propylene or R-CH=CH 2 olefins, where R is C 3 ~C 8 It is an alkyl or cycloalkyl (particularly ethylene, propylene or an α-olefin having 5 to 8 carbon atoms, such as pentene-1, hexene-1, 4-methylpentene-1 and octene-1).

[0035] The homopolymers and copolymers are 3 or titanium halide compounds supported on magnesium chloride (especially TiCl 4 The butene-1 can be obtained by low pressure Ziegler-Natta polymerization of butene-1 (with any comonomer) using a catalyst based on 1,2-diphenyl ether (Al) and a cocatalyst, especially an alkyl compound of aluminum. Electron donor compounds can be added to the catalyst components to adjust the polymer properties, such as the molecular weight and the degree of isotacticity. Examples of electron donor compounds include esters of carboxylic acids and alkylalkoxysilane esters.

[0036] In particular, the butene-1 homopolymers and copolymers A) can be prepared by polymerizing monomers in the presence of a stereospecific catalyst, which is preferably: (i) MgCl 2 a solid component comprising a Ti compound and an internal electron donor compound supported thereon; (ii) an alkylaluminum compound; and, optionally, (iii) an external electron donor compound.

[0037] Magnesium dichloride in active form is preferably used as a support. As is known from the patent literature, magnesium dichloride in active form is particularly suitable as a support for Ziegler-Natta catalysts. In particular, USP 4,298,718 and USP 4,495,338 were the first to describe the use of these compounds in Ziegler-Natta catalysts. As can be seen from these patents, magnesium dihalides in active form used as supports or co-supports in catalytic components for polymerizing olefins are characterized by an X-ray spectrum in which the most intense diffraction lines appearing in the spectrum of the inactive halides are attenuated in intensity and replaced by halos whose maximum intensity is shifted to a lower angle relative to the maximum intensity of the more intense lines.

[0038] The preferred titanium compound for use in catalyst component (i) is TiCl 4 and TiCl 3 and further having the formula Ti(OR) n-y X y Also usable are Ti-titanium haloalkoxides of the formula: where n is the valence of titanium, X is a halogen, preferably chlorine, and y is a number from 1 to n.

[0039] The internal electron donor compound is preferably selected from esters, more preferably from alkyl, cycloalkyl or aryl esters of monocarboxylic acids (e.g. benzoic acid) or polycarboxylic acids (e.g. phthalic acid, succinic acid or glutaric acid), the alkyl, cycloalkyl or aryl having 1 to 18 carbon atoms. Examples of the electron donor compound include diisobutyl phthalate, diethyl phthalate, dihexyl phthalate, diethyl or diisobutyl 3,3-dimethylglutarate. Typically, the internal electron donor compound is MgCl 2 The molar ratio to is 0.01 to 1, preferably 0.05 to 0.5.

[0040] The alkyl-Al compound (ii) is preferably selected from trialkylaluminum compounds, such as triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum. The trialkylaluminum compound is preferably selected from alkylaluminum halides, alkylaluminum hydrides or alkylaluminum sesquichlorides, such as AlEt 2 Cl and Al 2 Et 3 Cl 3 A mixture of may also be used.

[0041] The external donor (iii) preferably has the formula Ra 1 R b 2 Si(OR 3 ) c wherein a and b are integers from 0 to 2, c is an integer from 1 to 3, the sum of (a+b+c) is 4, and R 1 , R 2 and R 3 is an alkyl, cycloalkyl, or aryl having 1 to 18 carbon atoms, which may contain a heteroatom. Particularly preferred silicon compounds include those in which a is 0, c is 3, b is 1, and R 2 is a branched alkyl or cycloalkyl group which may contain heteroatoms; R 3 is methyl. Examples of such preferred silicon compounds include cyclohexyltrimethoxysilane, tert-butyltrimethoxysilane, diisopropyltrimethoxysilane and hexyltrimethoxysilane. Particularly preferably, hexyltrimethoxysilane is used.

[0042] The amount of the electron donor compound (iii) used is set so that the molar ratio of the organoaluminum compound to the electron donor compound (iii) is 0.1-500, preferably 1-300, and more preferably 3-100.

[0043] To make the catalyst particularly suitable for the polymerization step, the catalyst may be prepolymerized in a prepolymerization step. The prepolymerization may be carried out in liquid (slurry or solution) or gas phase, usually at a temperature below 100° C., preferably between 20 and 70° C. The prepolymerization step is carried out with a small amount of monomer, the duration being the time required to obtain a polymer, the amount of polymer being 0.5-2000 g / g solid catalyst component, preferably 5-500 g / g solid catalyst component, more preferably 10-100 g / g solid catalyst component.

[0044] As disclosed, for example, in WO 03 / 042258, butene-1 polymers can also be prepared by polymerization in the presence of a catalyst, the catalyst being obtained by contacting a metallocene compound with an aluminoxane.

[0045] The polymerization process can be carried out according to known techniques, such as slurry polymerization using a liquid inert hydrocarbon as diluent or solution polymerization using, for example, liquid butene-1 as reaction medium. Furthermore, the polymerization process can be carried out in the gas phase, operating in one or more fluidized or mechanically stirred bed reactors. It is highly preferred that the polymerization is carried out in liquid butene-1 as reaction medium.

[0046] To control molecular weight, molecular weight regulators, especially hydrogen gas, are provided to the polymerization environment.

[0047] Examples of polymerization catalysts and processes are disclosed in WO99 / 45043 and WO2004048424.

[0048] The butene-1 homopolymers and copolymers A) and the butene-1 polymer compositions of the invention are not particularly limited in molecular weight, but preferably they (both) have an MIE of 100 to 0.01, more preferably 10 to 0.1 g / 10 min, MIE being the melt flow index measured at 190° C. / 2.16 kg according to ISO 1133-2:2011. In particular, when used in extrusion units for producing tubing, an MIE in the range of 1 to 0.1 g / 10 min is preferred. High MIE values ​​can be obtained directly during polymerization or by subsequent chemical treatment of the polymer components (chemical viscosity reduction).

[0049] Chemical thinning destruction of the polymer is carried out in the presence of a radical initiator, such as a peroxide. Examples of radical initiators useful for this purpose include 2,5-dimethyl-2,5-di(peroxy tert-butyl)-hexane and dipentyl peroxide.

[0050] The butene-1 homopolymers and copolymers A) preferably have an intrinsic viscosity value measured in decalin at 135° C. of 1.5 to 4 dl / g.

[0051] The molecular weight distribution (MWD) of the butene-1 homopolymers and copolymers A) is not particularly critical and can usually fall within a wide range. However, for pipe applications, the MWD is w / M n (M w where MWD is the weight average molecular weight and Mn is the number average molecular weight), the MWD value measured by GPC analysis is preferably 4 or more, particularly preferably 5 or more.

[0052] In any case, the upper limit of the Mw / Mn value is preferably 9.

[0053] Generally, Mw / Mn values ​​greater than 5 are considered to correspond to a broad MWD.

[0054] Broad MWD butene-1 polymers can be obtained in several ways. One way is to use a catalyst capable of producing substantially broad MWD polymers when (co)polymerizing butene-1. Another possibility is to mechanically blend butene-1 polymers with sufficiently different molecular weights using conventional mixing equipment.

[0055] It is also possible to operate by a multi-stage polymerization process in which butene-1 polymers of different molecular weights are prepared in succession in two or more reactors with different reaction conditions, for example the concentration of molecular weight regulator fed to each reactor.

[0056] In the present invention, component B) is a talc characterized by the volumetric particle size distribution values ​​mentioned above.

[0057] Component B) of the present invention, in addition to said Dv(0.95) value, preferably has at least one of the following volumetric particle size distribution characteristics: Dv(0.99) is 100 μm or less, or 50 μm or less, or 30 μm or less, and in any case the lower limit is preferably 10 μm. Dv(0.90) is 20 μm or less, or 15 μm or less, and in either case the lower limit is preferably 3 μm. Dv(0.50) is 10 μm or less, or 8 μm or less, with the lower limit being preferably 2 μm. Dv(0.10) is 5 μm or less, or 4 μm or less, with the lower limit preferably being 1 μm.

[0058] The volumetric particle size refers to the diameter of an equivalent sphere having the same volume as the particle of interest.

[0059] Therefore, the value of the volume-based particle size distribution means that particles having a specified volume fraction (for example, 95% by volume for Dv(0.95)) have an equivalent diameter smaller than a predetermined value.

[0060] Such measurements are made by laser diffraction. The analytical device used is preferably a Malvern Mastersizer instrument.

[0061] Talc is known to be a magnesium silicate hydrate.

[0062] Usually, its formula is Mg 3 S 4 O 10 (OH) 2 It has been reported that.

[0063] In reality, talc is a mineral consisting primarily or essentially of said magnesium silicate hydrates, possibly associated with other mineral materials such as chlorite (magnesium aluminium silicate hydrate) and dolomite.

[0064] To obtain the particle size distribution values, the talc may be ground by known techniques such as grinding, e.g., with an air classifier mill, compressed air, steam, or impact milling.

[0065] Preferably, component B) does not contain any chemical additives, in particular does not contain any acid acceptors such as stearates, in particular metallic stearates, e.g. zinc stearate.

[0066] Preferred examples of ethylene polymers C) include those having a molecular weight of preferably 0.940 to 0.965 g / cm 3 High density polyethylene (HDPE) having a density of 0.900 to 0.939 g / cm 3 and linear low density polyethylene (LLDPE) having a density of 0.917 to 0.935 g / cm3 (both are usually obtained by low pressure polymerization), and preferably 3 Examples of low-density polyethylene (LDPE) include low-density polyethylene (LDPE) (usually obtained by high-pressure polymerization) having a density of 100 to 2000 nm. The low-pressure polymerization is usually carried out in the presence of the same type of Ziegler-Natta catalyst as described above, and the high-pressure polymerization is usually carried out in the presence of a radical initiator such as a peroxide.

[0067] The HDPE may be an ethylene homopolymer or an ethylene copolymer containing one or more olefin comonomers.

[0068] The LLDPE may be an ethylene copolymer containing one or more olefin comonomers.

[0069] The comonomer or comonomers present in the HDPE and LLDPE are typically of the formula CH 2 The olefin is selected from olefins having ═CHR, where R is a straight or branched alkyl group having 1 to 10 carbon atoms.

[0070] Specific examples include propylene, butene-1, pentene-1, 4-methylpentene-1, hexene-1, octene-1, and decene-1.

[0071] The preferred comonomer content in said HDPE (if present) is between 0.1% and 15% by weight, in particular between 0.5% and 10% by weight, relative to the total weight of the HDPE polymer.

[0072] The preferred comonomer content in the LLDPE is between 5% and 20% by weight, in particular between 8% and 15% by weight, based on the total weight of the LLDPE polymer.

[0073] The LDPE may be an ethylene homopolymer or an ethylene copolymer containing small amounts of a comonomer such as butyl propyleneate.

[0074] Among the ethylene polymers C), HDPE is particularly preferred.

[0075] Preferably, the ethylene polymer C) has an MIF of 1 to 50 g / 10 min, or 5 to 50 g / 10 min, in particular 10 to 40 g / 10 min, MIF being the melt flow index measured at 190° C. / 21.6 kg according to ISO 1133-2:2011.

[0076] It has become clear that the polybutene-1 compositions of the present invention may also contain other additives commonly used in the art, such as stabilizers, antioxidants, preservatives, processing aids, pigments and organic and inorganic fillers.

[0077] The polybutene-1 compositions of the present invention may be obtained by blending components A), B) and, optionally, C) using blending techniques and equipment well known in the art.

[0078] Thus, extruders known in the art can be used, including single screw extruders (conventional single screw extruders and CoKneaders (e.g. Buss)), twin screw extruders, mixers (continuous and intermittent). Such equipment may be equipped with separate feed systems used for each of components A), B) and C). Component B) and optional component C) can be added to the polymer mass in the blending equipment, in particular the extruder, at the same feed port or downstream of the point where A) is fed to the blending equipment, with a distance between both that allows A) to be in the form of a molten homogenous mass.

[0079] Component B) may be provided in the form of a masterbatch in a polymeric carrier, more preferably in a polyolefin carrier, in particular in a polybutene carrier similar to the butene-1 polymer component A).

[0080] Preferably, prior to the blending step, components A), B) and optionally C) are premixed. For the premixing step, any method and equipment used in the art can be used, in particular low speed mixers, such as single or double shaft paddle conveyors, ribbon blenders, plow mixers.

[0081] To obtain the final composition, a static mixer can also be used, such as Sulzer's SMX® static mixer, in which the molten streams of components (A), (B) and (C) are fed to its inlet and forced through using a gear pump, twin screw or single screw extruder.

[0082] The processing temperature during the blending step must be sufficient to bring (and maintain) component A) in a molten state, and, if A) is already in a molten state, to maintain it in the molten state when B) and, optionally, C) are added. Such temperatures are preferably in the range of 100°C to 230°C, more preferably 100°C to 220°C, and most preferably 120°C to 210°C.

[0083] As mentioned above, the preferred use of the polybutene-1 compositions of the present invention is in the manufacture of pipes, especially pipes for transporting water and heat flow media, and pipe joints, but in general, they can be advantageously used in any application requiring improved mechanical and processing properties.

[0084] The practice and advantages of various embodiments, compositions and methods according to this specification are disclosed in the following examples, which are illustrative only and are not intended to limit the scope of the invention in any manner.

[0085] Particle size distribution

[0086] Particle size distribution (PSD) is measured by laser diffraction according to ISO 13320:2009.

[0087] The instrument used is a Mastersizer® 2000 equipped with a sample dispersion unit manufactured by Malvern, UK.

[0088] The detection system has the following features: Red light: forward scatter, side scatter, back scatter; Blue light: wide-angle forward and backward scattering; Light source: Red helium neon laser; Blue light solid-state light source; Optical alignment system: Automatic high speed alignment system with dark field optical reticle; -Laser system: Class 1 laser product.

[0089] The PSD determination is based on the principle of optical diffraction where a laser monochromatic light is scattered through a dispersed particulate sample. The signal is received by a computer interfaced to the instrument, which processes the received signal and converts it into a dimensional physical quantity.

[0090] The results are presented as a PSD report of 106 class diameters (virtual screens), including cumulative percentage correlations for volume and other derived parameters.

[0091] The measurement data is contaminated by background electrical noise and scattering data from dust on the optical device and contaminants suspended in the dispersion medium, therefore it is necessary to ensure that the sample dispersion unit is clean and all trace impurities and residues are removed.

[0092] Therefore, a background measurement with pure dispersant (solvent) and an electrical background measurement are performed. The resulting total background value is subtracted from the sample measurement to obtain the true sample data.

[0093] For background measurements, 250 cc of anhydrous n-heptane solvent containing 2 g / 1 SPAN 80 Pure as an antistatic agent is introduced into the sample dispersion unit. Before each measurement, residual air in the solvent is removed by ultrasonic treatment (60 s).

[0094] The solvent is then pumped into the measurement cell while the stirrer and circulation pump are running in the power range of 2205 rpm.

[0095] measurement

[0096] The sample, suspended in anhydrous n-heptane by stirring, is added directly to the sample unit.

[0097] Circulation of the sample suspension is allowed for 2 min to facilitate the breakup of aggregates (if present).

[0098] The obscuration bar is displayed on the monitor and corresponds to the optimal volume concentration of the sample. The concentration of the sample must correspond to an obscuration value within the range of 10%-30%. This range ensures representative and stable results.

[0099] The refractive index (RI) is set as follows: Particle RI:1.596; Dispersant RI: 1.390.

[0100] The measurement time is 4 seconds.

[0101] The signal received from the laser device is processed and then the PSD is calculated using software provided with the Mastersizer device.

[0102] Crystallization and Melting Temperature

[0103] Crystallization temperature (T c ) and melting temperature values ​​are determined using the following procedure.

[0104] Differential scanning calorimetry (DSC) data are acquired using a Perkin Elmer DSC-7 instrument. A weighed sample (5-10 mg) is enclosed in an aluminum disk and heated to 200 °C at a scan rate equivalent to 10 °C / min. The sample is held at 200 °C for 5 min to completely melt all crystallites and thus eliminate the thermal history of the sample. It is then cooled to -20 °C at a scan rate equivalent to 10 °C / min and the peak temperature is taken as the crystallization temperature (T c ) and the area is the crystallization enthalpy. After standing for 5 min at -20°C, the sample was heated a second time to 200°C at a scan rate corresponding to 10°C / min. In this second heating run, the peak temperature is taken as the melting temperature of polybutene-1 crystalline form II (TmII) and the area as the melting enthalpy (ΔHfII).

[0105] To determine the melting temperature (TmI) of polybutene-1 crystalline form I, a sample is melted and held at 200°C for 5 minutes, then cooled to 20°C at a cooling rate of 10°C / min. The sample is then stored at room temperature for 10 days. After 10 days, the sample is subjected to DSC, cooled to -20°C, and then heated at 200°C with a scanning rate corresponding to 10°C / min. During this heating run, the first peak temperature from the low temperature side of the thermogram is taken as the melting temperature (Tml).

[0106] Crystallization half time at 90℃

[0107] Differential scanning calorimetry (DSC) data are obtained using a Perkin Elmer DSC-7 instrument. A weighed sample (5-10 mg) is enclosed in an aluminum disk and heated from room temperature to 180 °C at a scan rate corresponding to 10 °C / min.

[0108] The sample is kept at 180° C. for 5 minutes to completely melt all the crystallites and eliminate the thermal history of the sample.

[0109] It is then cooled to 90° C. at a scan rate corresponding to 60° C. / min and the heat flow due to the crystallization exotherm at 90° C. is measured. The integral of the heat transfer is recorded as a function of time until crystallization is complete, i.e., until heat transfer stops.

[0110] The crystallization half-time is the time at which the heat transfer integral reaches half its final value.

[0111] MIF and MIE

[0112] Determined at 190°C and a specified load in accordance with ISO 1133-2:2011.

[0113] intrinsic viscosity

[0114] It is determined in tetrahydronaphthalene at 135° C. according to standard ASTM D 2857-16.

[0115] Tensile modulus (MET-DMTA)

[0116] Determined on 1 mm thick compression molded plaques by dynamic mechanical thermal analysis (DMTA) at 23 °C according to ISO 6721-4:2019.

[0117] Flexural modulus

[0118] Measured after 10 days according to standard ISO 178:2019.

[0119] Izod impact resistance at 23°C and 0°C

[0120] Measured according to ISO 8986-2:2009 on compressed plaques according to IS0180:2000.

[0121] Comonomer Content

[0122] It is measured by IR spectroscopy or NMR.

[0123] Specifically for butene-1 copolymers, the amount of comonomer is 13 It can be calculated from the C-NMR spectrum.

[0124] An example of the analysis procedure is shown below.

[0125] 13 C NMR spectra were obtained on a Bruker AV-600 spectrometer equipped with a cryogenic probe. The spectrometer operates in Fourier transform mode at 120° C. and 150.91 MHz.

[0126] T βδ Carbon (CJ Carman, RA Harrington and CE Wilkes, Macromolecules 10, 3The peak at 37.24 ppm (based on the nomenclature of , 536 (1977)) is used as an internal standard at 37.24 ppm. Samples are dissolved in 1,1,2,2-tetrachloroethane-d2 at 8% wt / v concentration at 120 °C. Each spectrum is 1 H- 13 The data are collected with a 90° pulse with a 15 s delay between the pulse and the CPD to remove C coupling. Approximately 512 transients are stored in 32K data points using a 9000 Hz spectral window.

[0127] Evaluation of spectral distribution, triad distribution and composition Using the following terms, Kakugo [M. Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Large Molecules, 16, 4 , 1160 (1982)] and Randall [JC Randall, Macromol. Chem Phys. C30, 211 (1989)]. BBB = 100(T ββ ) / S= I5 BBE= 100T βδ / S= I4 EBE = 100 P δδ / S= 114 BEB = 100S ββ / S= 113 BEE= 100S αδ / S= 17 EEE = 100(0.25S γδ +0.5 S δδ ) / S= 0.25 19+ 0.5I10 Here, S = I5 + I4 + I14 +I13 + I7 + 0.25 I9 + 0.5I10

[0128] The total amount of 1-butene and ethylene, as a mole percentage, is calculated from the triad using the following relationship: [E] = EEE+BEE+BEB [B] = BBB+BBE+EBE [Table 1-1] [Table 1-2]

[0129] Determination of isotactic pentad content 13 C NMR spectra were acquired on polymer solutions (8% to 12% by weight) in deuterated 1,1,2,2-tetrachloroethane at 120 °C. 13 C NMR spectra were obtained on a Bruker AV-600 spectrometer equipped with a cryoprobe, operating in Fourier transform mode at 120 °C and 150.91 MHz. 1 H- 13 A 90° pulse with a 15 second delay between the pulse and the CPD (WALTZ 16) is used to remove C bonds. Approximately 512 transients are stored in 32K data points using a spectral window of 60 ppm (0-60 ppm). The mmmm pentad peak (27.73 ppm) is used as a reference. Partitioning is performed as in the literature (Asakura T., Large Molecules 1991, 24, 2334-2340). The percentage value of pentad tacticity (mmmm%) of butene-1 polymer is the percentage of stereoregular pentads (isotactic pentads) calculated from the relevant pentad signals (peak areas) in the branched methylene or born NMR region, as follows: mmmm% = 100 A1 / (A1+A2) Here, Al is the area between 28.0 and 27.59 ppm, A2 is the area between 27.59 and 26.52 ppm.

[0130] Fractions soluble and insoluble in xylene at 0℃ (XS-0℃)

[0131] 2.5 g of the polymer sample is dissolved in 250 ml of xylene at 135° C. with stirring. After 30 minutes, the solution is cooled with stirring to 100 °C, then cooled to 0 °C in a water and ice bath. The solution is then allowed to precipitate in the water and ice bath for 1 hour. The precipitate is filtered with filter paper. During filtration, the flask is placed in a water and ice bath to bring the temperature inside the flask as close as possible to 0 °C. After the filtration is completed, the filtrate temperature is equilibrated to 25 °C, the volumetric flask is immersed in a water flow bath for about 30 minutes, and then two 50 ml aliquots are divided. The solution aliquots are evaporated in a nitrogen gas stream and the residue is dried under vacuum at 80 °C until constant weight. The weight difference between both residues should be less than 3%. Otherwise, the test must be repeated. The weight percentage of the polymer solubles is then calculated from the average weight of the residues (xylene solubles at 0 °C = XS 0 °C). The insoluble fraction in o-xylene at 0 °C (xylene insolubles at 0 °C = XI % 0 °C) is: XI%0℃=100-XS%0℃.

[0132] X-ray crystallinity determination

[0133] X-ray crystallinity is measured using an X-ray powder diffractometer with fixed slit Cu-Kal radiation, taking spectra between diffraction angles 2θ=5° and 2θ=35° with a step of 0.1° every 6 seconds.

[0134] Measurements are performed on disk-shaped compression-molded specimens with a thickness of about 1.5 to 2.5 mm and a diameter of about 2.5 to 4.0 cm. These specimens are compressed in a compression press at a temperature of 200°C ± 5°C for 10 minutes without any noticeable pressure, and then compressed under a pressure of about 10 kg / cm. 2 Apply pressure for a few seconds and repeat the last operation three times.

[0135] Define a suitable linear baseline for the whole spectrum, calculate the total area (Ta) between the spectral profile and the baseline (expressed in counts / sec·2θ), and use the diffraction pattern to derive all components necessary for crystallinity. Then, along the whole spectrum, define a suitable amorphous profile that separates the amorphous and crystalline regions according to a two-phase model. Thus, the amorphous area (Aa) (expressed in counts / sec·2θ) may be calculated as the area between the amorphous profile and the baseline, and the crystalline area (Ca) (expressed in counts / sec·2θ) as Ca = Ta - Aa.

[0136] Next, calculate the crystallinity of the sample using the following formula: %Cr=100×Ca / Ta

[0137] GPC Determination of Mw / Mn by

[0138] Mn, Mw and derived Mw / Mn were determined using a Waters GPCV 2000 instrument equipped with a column set of four PLgel Olexis mixed gels (Polymer Laboratories) and an IR4 infrared detector (PolymerChar). The size of the columns is 300 × 7.5 mm, and their particle size is 13 μm. 1-2-4-trichlorobenzene (TCB) was used as the mobile phase, and its flow rate was kept at 1.0 ml / min. All measurements were performed at 150 °C. The solution concentration in TCB was 0.1 g / dL, and 0.1 g / l of 2,6-dibutyl-p-cresol was added to prevent decomposition. For GPC calculations, a general calibration curve was obtained using 10 polystyrene (PS) standard samples (peak molecular weight range 580-8.5 million) provided by Polymer Laboratories. The experimental data were interpolated using third-order polynomial fitting to obtain the relevant calibration curve. Data acquisition and processing were performed using Empower (Waters). The Mark-Houwink relationship was used to determine the molecular weight distribution and associated average molecular weight, with K values ​​of PS and PB being Kps = 1.21 × 10, respectively. -4dL / g and Kpb = 1.78 x 10 -4 dL / g, and for PS a Mark-Houwink exponent α=0.706 is used, and for PB a=0.725 is used.

[0139] For butene-1 / ethylene copolymers, the composition is assumed to be constant over all molecular weights for data evaluation, and the K value of the Mark-Houwink relationship is calculated using the linear combination: K EB =x E K PE +X P K PB Here, K eb is the copolymer constant, and K pe (4.06×10 -4 , dL / g) and K pb (1.78×10 -4 dl / g) is a constant for polyethylene and polybutene, and x e and x b are the ethylene and butene-1 weight percent contents. The Mark-Houwink index α=0.725 is used for all butene-1 / ethylene copolymers, regardless of composition.

[0140] density

[0141] Determined at 23 °C according to standard ISO 1183-1:2019.

[0142] Examples 1 and 2 and Comparative Example 1

[0143] Materials used in the examples PB-1: butene-1 homopolymer having the characteristics listed in Table 1 Talc 1: Talc having a particle size distribution by volume as set forth in Table 2. Free of additives, marketed under the trademark HM05 by the company Imi Fabi. Talc 2: Comparative zinc stearate coated talc. having a volumetric particle size distribution as set forth in Table 2 and marketed by Imerys under the trademark Mistron zsc. HDPE: 0.954 g / cm 3 and an MIF of 24 g / 10 min.

[0144] The materials are melt blended in a Leistritz Micro 27 extruder with co-rotating twin screws, 27 mm screw diameter segments, a 40:1 L / D ratio, and a maximum screw speed of 500 rpm.

[0145] Main extrusion parameters: Temperature: 200℃; Screw speed: 200 rpm; Output: 15kg / h.

[0146] The component amounts and properties of the final compositions thus obtained are shown in Table 3. [Table 2] [Table 3] [Table 4]

Claims

1. A) 97.5% to 99.85% by weight, based on the total weight of A) and B), of a polymer composition selected from butene-1 polymers, or crystalline butene-1 homopolymers, copolymers, or combinations thereof; B) 0.15% to 2.5% by weight, based on the total weight of A) and B), of talc in particulate form having a volume-based particle size distribution Dv(0.95) determined by laser diffraction of less than or equal to 25 μm, in each case with a lower limit of 5 μm, and optionally C) 0.01% to 2% by weight of an ethylene polymer; The amount of C) means the total weight of A)+B)+C), which totals 100% of the butene-1 polymer composition.

2. The talc B) has the following additional characteristics of a volumetric particle size distribution: Dv(0.99) is equal to or less than -100 μm, with the lower limit being 10 μm; Dv(0.90) is equal to or less than -20 μm, with the lower limit being 3 μm; Dv(0.50) is equal to or less than -10 μm, with the lower limit being 2 μm; Dv(0.10) is less than or equal to -5 μm, with the lower limit being 1 μm 2. The butene-1 polymer composition of claim 1, comprising at least one of:

3. Crystallization temperature T of 80° C. or higher c having The crystallization temperature T c is measured by DSC method at a scanning rate of 10° C. / min after one melt cycle.

4. It has a melting temperature of 90°C to 125°C, 3. The butene-1 polymer composition according to claim 1 or 2, wherein said melting temperature is measured by DSC method at a scanning rate of 10° C. / min during the second heating run after the first melting and cooling.

5. having an MIE of 100 to 0.01 g / 10 min; 3. The butene-1 polymer composition according to claim 1 or 2, wherein said MIE is the melt flow index measured at 190°C / 2.16 kg according to ISO 1133-2:2011.

6. The following additional features: Crystallization half time of 90 to 160 seconds at -90°C; - a flexural modulus of 450 to 650 MPa, measured according to ISO 178:2019 after 10 days of molding; - a tensile modulus of 500 to 800 MPa, measured on a 1 mm thick compression molded plate by DMTA analysis at 23 ° C according to ISO 6721-4: 2019; - 3 to 15 kJ / m2 measured according to ISO 180:2000 on compressed plaques according to ISO 8986-2:2009 2 Izod impact resistance value at 23° C. - 2 to 10 kJ / m2, measured according to ISO 180:2000 on compressed plaques according to ISO 8986-2:2009 2 Izod impact resistance value at 0°C The butene-1 polymer composition according to claim 1 or 2, comprising at least one of:

7. Component A) of the butene-1 polymer has a crystallization temperature T c having The crystallization temperature T c is measured by DSC method at a scanning rate of 10° C. / min after one melt cycle.

8. The butene-1 homopolymers and copolymers A) have an isotacticity of 90% to 99%; The butene-1 polymer composition according to claim 1 or 2, wherein said degree of isotacticity is measured in mmmm pentads / total pentads using NMR analysis.

9. The butene-1 polymer composition according to claim 1 or 2, wherein the ethylene polymer component C) is selected from HDPE, LLDPE, LDPE and mixtures thereof.

10. An article comprising the polyolefin composition of claim 1 or 2.

11. 11. The article of claim 10 in the form of a tube or a tube joint.

Citation Information

Patent Citations

  • Poly-1-butene resin composition, and pipe material and pipe prepared therefrom

    JP2002256124A

  • Polybutene resin composition

    JP2007186563A

  • Polypropylene composition for oriented articles

    JP2009520093A

  • Polyethylene for pipe and joint and molded body of the same

    JP2016194060A

  • Polypropylene Compositions for Stretched Articles

    US20100233399A1